Efeito da Clonidina associada à Lidocaína na anestesia subtenoniana (Episcleral) em cirurgia de catarata - Sigmar Aurea Cabral (2012)
Cataract surgery is the most common surgical procedure in ophthalmology, and regional anesthesia is commonly used. Among the techniques of regional, subTenons (episcleral) anesthesia is becoming more used because it provides better akinesia and analgesia. Clonidine is a receptor agonist adrenergic , often used as an adjuvant and periocular retrobulbar block, extending the akinesia and the analgesia. The objective of this study was to evaluate whether the addition ofclonidine and lidocaine 2% in sub-Tenons anesthesia interferes with the duration of the blockade and analgesia in patients undergoing cataract surgery. In this prospective, randomized, double blind study included 40 ASA I and II, from both genders, randomly divided into 2 groups of 20 patients, to whom was administered, in the control group, 6 mL of lidocaine 2%, associated with 1 mL of sodium chloride 0.9%, and, to the clonidine group, lidocaine associated 6 mL of 1 µg/kg of clonidinediluted in 1 mL of sodium chloride at 0.9%. Both solutions without epinephrine and associated with 25 IU/mL hyaluronidase. During the perioperative and postoperative we assessed mean arterial pressure, heart rate, peripheral oxygen saturation and sedation. The akinesia of the eye movements in four directions of gaze, levator palpebrae muscles and orbicularis were evaluated at 1 minute (M1), 4 minutes (M4) and 8 minutes (M8) after the administration of the anesthetic. Scores of motility 0-2 were used, where 0 = no movement, 1 = partial movement, and 2 = normal movement. The total sum of the scores was 12 points, with scores 3 satisfying for the surgery. For evaluation of pain intensity rating scale was used numerical (0-10), where 0 = no pain, and 10 = maximum pain, measured during the blockade, administration of the anesthetic, peri and postoperatively. We also evaluated the consumption of analgesic and adverse effects. It was observed that the start time isearlier in akinesia clonidine, not statistically significant compared to control.Moreover, the duration of sensory anesthesia, akinesia muscle of the eye, and lift eyelid were significantly prolonged for the orbicular clonidine. Likewise, the duration of analgesia was higher in the clonidine, with more intense pain in the control group. The time to first analgesic requirement was also higher in the clonidine group. Weconclude that clonidine (1 µg/kg) plus 2% lidocaine sub-Tenons anesthesia in cataract surgery lasted more efficiently the duration of sensory anesthesia, akinesia, analgesia and time from the first request for postoperative analgesics, with few adverse effects.